Anatomical education and its innovations: an interdisciplinary, hands-on, team-building approach - Zuccaro, Mina; Girolamo, Francesco (Italian Journal of Anatomy and Embryology, 2024)
Contemporary approaches in anatomical education, such as problem-based learning, case-based learning, and the flipped classroom, grounded in evidence and tailored to student needs, have demonstrated marked enhancements in student engagement and interactions. These methodologies shift the educational focus from passive knowledge transmission to active knowledge construction by students, fostering task-oriented learning. This inquiry explores the implementation of a dynamic, multimodal, and engaging learning approach to teach second-year MBBS students about musculoskeletal and splanchnic anatomy at the School of Medicine, The University of Bari ‘Aldo Moro’, Bari, Italy. Additionally, it investigates student perceptions regarding anatomy learning and traditional lectures, along with their views on participating in problem-based learning sessions. In these problem-based learning sessions, small groups of students engage in discussions, formulate hypotheses, establish learning objectives in anatomy, and virtually dissect human bodies using the Anatomage Table. This innovative approach provides a comprehensive view of the anatomy of the body region, aiding the exploration of structures relevant to the symptoms presented by patients described in the problem-based learning sessions. The academic performance of students exposed to active learning is compared with that of their more traditionally taught counterparts. Our findings underscore the efficacy of employing an active, multimodal, and engaging learning strategy based on Anatomage-enhanced problem-based learning as a potent additional tool in anatomy education. To further validate these outcomes, future research endeavors should include randomized controlled trials, aiming to assess the comparative effectiveness of different learning strategies that have the potential to advance medical education.